2015
DOI: 10.3892/ijo.2015.3222
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome sequencing of human breast cancer reveals aberrant intronic transcription in amplicons and dysregulation of alternative splicing with major therapeutic implications

Abstract: Abstract. Advances in genomic and transcriptome sequencing are revealing the massive scale of previously unrecognised alterations occurring during neoplastic transformation. Breast cancers are genetically and phenotypically heterogeneous. Each of the three major subtypes [ERBB2 amplified, estrogen receptor (ESR)-positive and triple-negative] poses diagnostic and therapeutic challenges. Here we show, using highresolution next-generation transcriptome sequencing, that in all three breast cancer subtypes, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Splice variants of the AR and ESR1 are frequently found in prostata (Wadosky and Koochekpour 2016 ; Karantanos et al 2015 ) and breast cancer (Hu et al 2014 ; Forootan et al 2016 ), but are as well found in the brain of mammals including humans (Hu et al 2014 ; Ishunina et al 2013 ; Kundu et al 2015 ). AR splice variants have not been analyzed in birds.…”
Section: Receptor Structure: Species Differences and Tissue-specific mentioning
confidence: 99%
“…Splice variants of the AR and ESR1 are frequently found in prostata (Wadosky and Koochekpour 2016 ; Karantanos et al 2015 ) and breast cancer (Hu et al 2014 ; Forootan et al 2016 ), but are as well found in the brain of mammals including humans (Hu et al 2014 ; Ishunina et al 2013 ; Kundu et al 2015 ). AR splice variants have not been analyzed in birds.…”
Section: Receptor Structure: Species Differences and Tissue-specific mentioning
confidence: 99%
“…Alternative splicing generates multiple gene transcripts and consequently relevant protein isoforms, expanding biological complexity and protein functionality [35] . Several splicing events in breast cancer modulate disease biology and progression [ 36 , 37 ]. We have previously identified RANK-c as an alternatively spliced transcript of the TNFRSF11A gene with a role in NF-κB regulation and breast cancer aggressiveness [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Most RNA-Seq analytics ignore alternative splicing patterns despite recent evidence that alternative splicing is implicated in nearly a third of common diseases. In cancer, a tumor often displays dysregulation of the cellular machinery that controls alternative splicing (Yoshida et al, 2011; Kaida et al, 2012; Ladomery, 2013; Forootan et al, 2016). Yet, the clinical interpretation of alternative splicing patterns lies largely unexplored.…”
Section: Introductionmentioning
confidence: 99%